Variations of Sundanese in Agrarian Societies in Central Java - Mutmainah, Sevia; Fahrani Almira Rizkya Haryanto; Dwi Astuti; Shafira Anggraeni Kismanto; El Fathia Raisya Qonitulhaq; Eko Muharudin (Athena: Journal of Social, Culture and Society, 2024)
The purpose of this study is to describe the differences in language variations, explain the history of language development, and describe the differences in language variations in the agrarian society in Central Java. The problem that arises is how is the language variation, the history of development and the difference in language variation in the agrarian society in Central Java?. This research is qualitative with an approach that uses sociology and dialectology.qualitative approach. The data collection technique is by recording a list of questions and answers from informants directly or in writing. Then record images and sounds using a mobile phone. The results of the study show that there are two language variations, namely Sundanese and Javanese. Comparison of language variations in agrarian societies in Central Java includes phonology, morphology and lexicals.